Illocutionary Acts of Thomas Brag on Yes Theory Channel on Youtube - Frans Sayogie; Moh. Supardi; Farhan Razzak Oktalianza; Novian Halim Pratama (Budapest International Research and Critics University, 2022)
This paper aims to identify the illocutionary act types which were performed by Thomas Brag from a Canadian digital media which has been growing around on Yes Theory YouTube Channel. The method used in this paper is the descriptive qualitative and using Searle’s speech act theory. The subject of this research was a video that was uploaded by Yes Theory’s channel on YouTube. In analysing the data, the writers have taken most of the interactional conversations of Thomas Brag’s viewers and also his speaking partner making Thomas be able to deliver various information regarding the country that he has travelled to what was seen from the video. The illocutionary acts performed by Thomas Brag were classified and analysed using Searle’s theory. The result indicates that there were five of the illocutionary acts that were being performed by Thomas Brag. These speech acts on the video are giving proper information, being interactive, and positively impacting the change of the world. The interaction between Thomas Brag and his viewers make his Yes Theory YouTube Channel having many viewers in each of his videos. In conclusion, the communications that are built on this YouTube channel are very interesting and joyful keeping the viewers interested.